The Roles of an Effective Supervisor in Technical and Vocational Education and Training - Nehemiah Marwa, John; Jambari, Hanifah; Taman, Ishak; Hazirah Noh@Seth, Nur; Zolkifli Abdul Hamid, Mohd; Rasidi Pairan, Mohamad; Aini Mohd Ahyan, Nurul (International Journal of Psychosocial Rehabilitation, 2020)
This paper is focusing on the roles of effective supervision in TVET. Supervision is designed to promote teaching and learning activities, particularly in universities, colleges, and schools. TVET supervisees relay on the instructions of their teachers, instructors, and supervisor, whose duty it is to teach, direct, advise, and guide them in the acquisition of skills, knowledge, and attitudes that will make them to become quality graduates after leaving school. However, the study adopted a systematic review approach to search for relevant literature, TVET supervision, types of supervision in TVET education, and roles of a TVET supervisor, such as the key words used for the selection of the relevant literature, from data web-based providers such as Web of Science, Scopus, Google Scholar, and an online library. From which the results of the study revealed the appropriate roles of a TVET supervisor in education, such as a good relationship process or interpersonal relationship, learning needs, consultation and appointment, experience, training and personality, monitoring and implementation, among others. It is therefore recommended that teachers or supervisors embrace the revealed roles of the study in guiding their supervisees for effectiveness in their career pursuit.